Rohingya’s Genocide: Human Rights and Politics - Tomar, Prachi; Pandey, Aditya (Kathmandu School of Law Review, 2018)
The Rohingya’s most persecuted ethnic minority, practicing Sunni Islam, traces their origin from Arakan kingdom. The present democratic government of Myanmar and previous military junta have practiced ethnic cleansing and denies to grant citizenship to Rohingya’s making them stateless. There has been great violation against this ethnic group by the Myanmar government in one or the other way like restriction on freedom of movement religious choice, unemployment, education, marriage and family planning. On the contrary the present de facto leader of Myanmar has totally denied such ethnic cleansing and brushed away the criticism of her not handling the crisis. This paper tries to understand the dynamics and severity involved, the origin of the ethnic tension, the exclusionary policies of the government and also examines the abuse, discrimination and gross human rights violation of Rohingya Muslims which leads to the politicization of the issue and vice-versa i.e. how politicization of the issue leads to gross human rights violation. This paper further analyzes the pattern of violation, international politics and the political and economic interest vested which contributed to forced displacement in Myanmar not only of the Rohingya’s but other minorities like the Shan, the Kachin, the Karen and how this crisis has fi red up the political debate in the neighboring countries and has become a political contention and concludes with recommendation to be taken by the government and international organization to improve the situation of the minorities in Myanmar.